Personal ornaments, Neolithic groups and social identities: some insights into Northern Italy - Roberto Micheli (Documenta Praehistorica, 2012)
Personal ornaments are often used to display information about the person wearing them – identity, group or individual, status, current role. In this paper, I analyse ornaments from osseous raw materials from Early and Middle Neolithic sites in Serbia. The exotic origin and labour and skill invested in their production may have conferred value on them or added to it and their animal origin was considered of special significance. Specific forms conveyed information on status and/or social identity (membership of kin or social group, etc.) and their white colour probably had more than mere aesthetic significance.